Comparison of health-related quality of life in rheumatoid arthritis, psoriatic arthritis and psoriasis and effects of etanercept treatment. Issue 7 (17th January 2012) - Strand, Vibeke; Sharp, Veronika; Koenig, Andrew S; Park, Grace; Shi, Yifei; Wang, Brian; Zack, Debra J; Fiorentino, David
Abstract : Objectives: To compare health-related quality of life (HRQoL) before and after treatment with etanercept in patients with moderate to severe rheumatoid arthritis (RA), psoriatic arthritis (PsA) and psoriasis using spydergram representations. Methods: Data from randomised, controlled trials of etanercept in patients with RA, PsA and psoriasis were analysed. HRQoL was assessed by the medical outcomes survey short form 36 (SF-36) physical (PCS) and mental (MCS) component summary and domain scores. Baseline comparisons with age and gender-matched norms and treatment-associated changes in domain scores were quantified using spydergrams and the health utility SF-6D measure. Results: Mean baseline PCS scores were lower than age and gender-matched norms in patients with RA and PsA, but near normative values in patients with psoriasis; MCS scores at baseline were near normal in PsA and psoriasis but low in RA. Treatment with etanercept resulted in improvements in PCS and MCS scores as well as individual SF-36 domains across all indications. Mean baseline SF-6D scores were higher in psoriasis than in RA or PsA; clinically meaningful improvements in SF-6D were observed in all three patient populations following treatment with etanercept. Conclusions: Patients with RA, PsA and psoriasis demonstrated unique HRQoL profiles at baseline. Treatment with etanercept was associated with improvements in PCS and MCS scores as well as individual domain scores in patients with RA, PsA and psoriasis.